Influencia de las relaciones interpersonales de los usuarios en la participación de los programas en el centro del adulto mayor Guadalupe - Provincia de Pacasmayo: 2017. - Yepez Garamendi, Grecia Alexandra (2018)
This thesis was carried out with the aim to explain the influence of the interpersonal relations between users on the participation of the programs in the Center of the Older Adult Guadalupe - Pacasmayo Province: 2017. It has been considered the type of applied research, on the basis of an explanatory design, has applied the methods and techniques of quantitative and qualitative research, the sample consisted of 44 users of the Program of the Older Adult. The results obtained in the investigation, it can be deduced that have poor interpersonal relations due to the low level of communication, lack of confidence, poor leadership and poor motivation among users who become the main factors that limit their participation in the activities programd in the center of the Older Adult Guadalupe. With this study we intend to provide information, to promote social programs aimed at the family and institutions benefactors for the solution of this social problem. As social workers we must promote an excellent quality of life through a process of aging with integral health and quality of life.